Blast effects on buildings design of buildings to optimize resistance to blast loading - Mays, Geoffrey; Smith, P. D. (T. Telford, 1995)
Explains the approach to the design of buildings to optimize their resistance and to provide techniques for maximizing the potential of a building to give protection against explosive effects. This guide incorporates the design objectives concerning the protection of people and equipment, and the minimizing of damage to buildings.